2019
DOI: 10.18632/aging.102591
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NNT-AS1 enhances the malignant phenotype of bladder cancer by acting as a competing endogenous RNA on microRNA-496 thereby increasing HMGB1 expression

Abstract: The long noncoding RNA nicotinamide nucleotide transhydrogenase antisense RNA 1 (NNT-AS1) is a key malignancy regulator in a variety of human cancers. In this study, we first measured the expression of NNT-AS1 in bladder cancer and examined its role in cancer progression. The mechanisms behind the oncogenic functions of NNT-AS1 in bladder cancer were explored. We found that NNT-AS1 was upregulated in bladder cancer tissues and cell lines. This increased expression demonstrated a significant correlation with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Many studies have found that the expression level of NNT-AS1 is related to the prognosis of tumor patients. Studies on NSCLC [17], gastric cancer [32], HCC [21], cervical cancer [25,26], and bladder cancer [30] have shown that high-levels of NNT-AS1 were poor prognostic factors to reduce overall survival (OS). In addition, for CAA and osteosarcoma, up-regulated NNT-AS1 was reported to be significantly associated with reduced OS and disease-free survival (DFS) [22,24,27].…”
Section: The Diagnostic or Prognostic Value Of Aberrant Nnt-as1 Exprementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have found that the expression level of NNT-AS1 is related to the prognosis of tumor patients. Studies on NSCLC [17], gastric cancer [32], HCC [21], cervical cancer [25,26], and bladder cancer [30] have shown that high-levels of NNT-AS1 were poor prognostic factors to reduce overall survival (OS). In addition, for CAA and osteosarcoma, up-regulated NNT-AS1 was reported to be significantly associated with reduced OS and disease-free survival (DFS) [22,24,27].…”
Section: The Diagnostic or Prognostic Value Of Aberrant Nnt-as1 Exprementioning
confidence: 99%
“…In bladder cancer, NNT-AS1 can serve as the ceRNA of miR-496 and increase the expression of the downstream gene HMGB1 [30]. In breast cancer, NNT-AS1 inhibits miR-142-3p competitively, thereby promoting the expression of ZEB1, which in turn induces the proliferation and metastasis of cancer cells [36].…”
Section: Other Cerna Mechanisms Of Nnt-as1mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other pathways including PI3K/Akt/mTOR and Wnt/β-catenin signaling pathway were also found involved in the tumorigenesis and progression [26,15]. Besides, NNT-AS1 was capable of serving as a competing endogenous RNA (ceRNA) by sponging miR-485/BCL9 or miR-203 in cholangiocarcinoma [31,32], miR-1301-3p/PODXL or miR-496/HMGB1 in bladder cancer [3,33], miR-142-3p/ZEB1 in breast cancer [19], miR-424/E2F1 or miR-363 in gastric cancer [28,8], miR-22-3p/YAP1 or miR-129-5p in non-small cell lung cancer [34,30], and miR-320a in osteosarcoma [27], therefore alteration in cancer cell function resulting from NNT-AS1 downregulation may be rescued by miRNA inhibition. Notably, NNT-AS1 also showed a high expression level in drug-resistant NSCLC, which promoted the cisplatin resistance of cancer cells via the MAPK/Slug pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…The alarmin HMGB1 is released by most types of tumor cells and is detected in the serum of many cancer patients [40][41][42][43][44]. HMGB1 is ubiquitous in the TME and can interact with a variety of inflammatory cells to produce different results.…”
Section: Hmgb1mentioning
confidence: 99%